Eritromelalgija - Košak, Robert (Medicinski razgledi, 1999)
Erythromelalgia is a rare syndrome characterised by attacks of severe burning pain, erythema, and warmth of the extremities-primarily the feet and, to a lesser extend, the hands. The distress is induced by environmental heat, exercise, and dependency; it is relieved by exposure to cold and elevation of the extremity idiopathic and secondary forms of erythromelalgia exist. Secondary erythromelalgia has been linked to a wide variety of diseases, the most common of which are certain myeloproliferative disorders. This type affect aduns only, and is dramaticcally ameliorated by small doses of aspirin.Intravascular pratelet, with plugging of arterioles have been suggested as the cause of erythromelalagia in nyeloproliferative disorders. The pathogenesis of idiopathic forms has not yet been delineated.
Keywords: eritromelalgija; Erythromelalgia; Etiology; bolezni; disease; zdravljenje; Diagnosis; Therapy; diagnostika